Transformation of Veterinary Education through the Flipped Classroom Model: Advantages, Challenges, and Future Implications - Rajasekaran, Ranjani; Padmanath, K; Sasikumar, S; Richard Jagatheesan, P N (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Veterinary education is undergoing a significant transformation, with the adoption of the flipped classroom model at its forefront. This  innovative pedagogical approach challenges the traditional teaching method by reversing the sequence of instruction. In the flipped  classroom, students engage with pre-recorded lectures and readings independently before attending in-person class sessions, which are  now dedicated to active learning, group discussions, problem-solving, and practical application. The model's adoption aligns seamlessly  with the broader shift towards student-centered, outcome-based education, equipping veterinary students with essential skills and  knowledge for their dynamic profession. While the flipped classroom presents numerous advantages, it is not without challenges,  including technology requirements, instructor time investment, and the need to address resistance to change. Nevertheless, the  transformative potential of the flipped classroom in veterinary education is promising, emphasizing lifelong learning and adaptability  in an ever-evolving field. This shift, enabled by technology and innovative teaching strategies, prepares veterinary graduates to excel  in their profession's dynamic landscape.
Keywords: Active learning; Flipped classroom; Technology in education; Transformative teaching; Veterinary education